Projeto do subsistema de comunicação e distribuição e da camada de serviços da arquitetura OpenReality para suporte à criação de aplicações de visualização distribuída - Baptista, Bruno do Amaral Dias (2004)
This work presents the information distribution model adopted within OpenReality architecture (OR), and the related issues of its structures integration. Distributed Visualization Applications can be created using OR framework, which permits redefinitions, specializations and customizations. During distributed visualization application development, it s possible to choose the communication protocol to be used and its parameters. The consistency and interactivity concepts and their behavior for each information distribution model are also discussed. Among the main used structures is JAMP Platform (Java Architecture for Media Processing), which was upgraded to support OR requirements. JNDS application domain framework and JAMP2C development tool were added to JAMP development package. In a general way, the contribution of this project is to offer a new method for creating distributed visualization applications. Besides, this work improves the maturity of JAMP Platform, which now has a new framework and a new development tool available.